PERAN ORMAS ISLAM DALAM MENJAGA STABILITAS POLITIK SOSIAL BUDAYA INDONESIA PASCA PEMILU 2019 (KAJIAN PUSTAKA PADA ORGANISASI ISLAM TERBESAR NU DAN MUHAMMADIYAH) - Septian Arif Budiman; Mulyer Mananda Setyahadi (Jurnal Renaissance, 2019)
This study aims to find out empirically the role of two large organizations namely Nahdhalatul Ulama and Muhammadiyah in maintaining the socio-cultural repertoire in Indonesia after the 2019 ELECTION, this study uses qualitative methods with a literature review approach and various sources related to research, but the result is several meetings the leaders of political parties and national figures and Muslims led by the two organizations, this proves the role and khittah in maintaining unity as a form of characteristic of Indonesian society is still well implemented by the two largest Islamic organizations in Indonesia.